The Relationship between Knowledge and Medication Compliance Behavior among Patients with Tuberculosis - Hidayat, Jufri; Lee, Mei-Chen; Lee, Ming-Der; Chen, Chen-Hsiu (South East Asia Nursing Research, 2020)
Tuberculosis (TB) remains the highest priority among infectious diseases in the world today with increasing morbidity and mortality every year. Adherence to treatment plays an important role in the success of therapy among TB patients. This study aims to explore the relationship between demographic characteristics, knowledge, and medication compliance behavior among patients with tuberculosis in Indonesia. This study was descriptive correlational and cross-sectional design with the total sample was 150 tuberculosis confirmed in Medan Pulmonary Hospital, Indonesia. In this study found that there is a significant relationship between ethnicity and medication adherence (continues variable) with p = 0.01. Meanwhile when medication compliance behavior was treated as categorical variables, a significant relationship was found between medication compliance behavior and medical history (p = 0.03), smoking (p = 0.005), and alcohol (p = 0.03) among tuberculosis patients in Indonesia. In the multivariate analysis, multiple linear regression was performed which surprisingly shows that education was significantly associated with knowledge of TB (p = 0,02), and ethnicity (0.04).